Diesel Alkanes Are Incorporated and Metabolized in Ulva Lactuca Activating the Expression and Activities of Antioxidant Enzymes and Alkane-Metabolizing Enzymes - Moenne-Munoz, A; Gonzalez-Figueroa, A (Elsevier B.V., 2025)
To analyze whether the marine alga Ulva lactuca can incorporate and metabolize linear hydrocarbons (alkanes) of diesel, the alga was cultivated without diesel (control) or with 2.5 % v/v of diesel for 168 h (7 d). The concentration of alkanes in the culture medium decreased by 83 % at 168 h of culture while in algal tissue alkane levels increased to a maximal level at 24 h and decrease in 78 % at 168 h of culture. Diesel was constituted by alkanes from C7 to C28, mainly by alkanes C14 to C21 which represents 73 % of total alkanes. In algal tissue, the concentration of alkanes showed a maximal level at 24 h and alkanes C13 and C14 decreased in 100 % at 168 h, alkanes C15 and C16 decreased in 98 and 92 %, respectively at 168 h, and alkanes C18 and C21 decreased around 60 %. Thus, U. lactuca probably metabolizes main diesel alkanes in 60 % to 100 % at 168 h of culture. The incorporation of alkanes induced an oxidative stress condition characterized by an increase in superoxide anions and hydrogen peroxide levels that was rapidly mitigated by the increase in the level of antioxidant molecules such as ascorbate and glutathione, and the increase in activities of antioxidant enzymes such as SOD, AP, DHAR and GR showing maximal activities at 24 h of exposure. The expression and activities of alkane-metabolizing enzymes such as alkane monooxygenase, alcohol dehydrogenase and aldehyde dehydrogenase were increased, indicating that they may be involved in the metabolization of alkanes into fatty acids to fuel basal metabolism. Thus, the alga U. lactuca may constitute a useful biotechnological tool to remove diesel from seawater. © 2025 Elsevier B.V.